El plano irracional externo en Tucídides: τύχη, παράλογος, άvέλπιστος, άστάθυμητος, α - Muñoz Llamosas, Virginia (Gerión. Revista de Historia Antigua, 2001)
In Thucydides’ work the most impor tant cause in historic events in human nature , enclosing both a rational and a ir rational side. Beside this we have another ir rational factor, exter nal instead of inter nal, designated by lexical items such as , , , µ, o . The aim of this work is to study these lexical items in order to deter mine exactly how Thucydides undestands this ir rational external factor, whether Man can subject it to reason, and its relation with traditional gods. 1.